Association Between Folate and Health Outcomes: An Umbrella Review of Meta-Analyses - Bo, Yacong; Zhu, Yongjian; Tao, Yuchang; Li, Xue; Zhai, Desheng; Bu, Yongjun; Wan, Zhongxiao; Wang, Ling; Wang, Yuming; Yu, Zengli (Frontiers in Public Health, 2020)
Background: There is no study that has systematically investigated the breadth and validity of the associations of folate and multiple health outcomes. We aimed to evaluate the quantity, validity, and credibility of evidence regarding associations between folate and multiple health outcomes by using umbrella review of meta-analysis. Methods: We searched the Medline, Embase and Cochrane Library databases from inception to 20 May 2018 to identify potential meta-analyses that examined the association of folate with any health outcome. For each included meta-analysis, we estimated the summary effect size and their 95% confidence interval (CI) using the DerSimonian and Laird random effects model. We used the AMSTAR 2 (A Measurement Tool to Assess Systematic Reviews) to assess methodological quality and the GRADE (Grading of Recommendations, Assessment, Development and Evaluation working group classification) to assess the quality of evidence for each outcome included in the umbrella review. Results: Overall, 108 articles reporting 133 meta-analyses of observational studies and 154 meta-analyses of randomised controlled trials (RCTs) were included in the study. Among them, 108 unique exposure-outcome–population triplets (referred to as unique meta-analyses hereafter) of RCTs and 87 unique meta-analyses of observational studies were re-analysed. Beneficial effects of folate were observed in the all-cause mortality rate and in a number of chronic diseases, including several birth/pregnancy outcomes, several cancers, cardiovascular disease and metabolic-related outcomes, neurological conditions and several other diseases. However, adverse effects of folate were observed for prostate cancer, colorectal adenomatous lesions, asthma or wheezing, and wheezing as an isolated symptom and depression. Conclusions: Current evidence allows for the conclusion that folate is associated with decreased risk of all-cause mortality and a wide range of chronic diseases. However, folate may be associated with an increased risk of prostate cancer. Further research is warranted to improve the certainty of the estimates.